SISTEM PENGELOLAAN DAN KONTRIBUSI HUTAN RAKYAT DI DESA TAMBAKBAYA KABUPATEN KUNINGAN - Kosasih, Dede; Hidayat, Feri; Hendrayana, Yayan (Wanamukti: Jurnal Penelitian Kehutanan, 2024)
ABSTRACTCommunity forests are a type of natural resource management capital initiated by the community, namely community forests that are built independently by the community, intended for the production of wood or forest products, accompanied by economic goals in order to increase community income and welfare. One of the villages in Kuningan Regency, namely Tambakbaya Village, is a village that manages community forests with an area of 72,884 ha. Tambakybaya Village is a community forest location that is easy to reach and is supported by lots of public transportation with good roads to traverse. This research was carried out from March 2022 to July 2022 in a 9 ha community forest in Tambakbaya Village, Garawangi District, Kuningan Regency. The data collection method in this research uses interviews, while the data analysis method uses a Likert scale and analyzes the contribution of forests to toll revenues and the contribution to the UMR. The community forest management system in Tambak Baya Village with a monoculture system is in the medium category. The polyculture system is only found in the people's management system. The polyculture system is only found in land preparation activities, plant spacing, weeding, fertilizing, pruning and harvest preparation which are included in the good category. The contribution of community forests to total community income is 22,460,042 with a percentage of 18.1%, while the minimum wage for Kuningan Regency is 18.6%